25 Real world prescribing strategies for patients with an indication for oral anticoagulation undergoing percutaneous coronary intervention. (16th October 2019) - Fitzgerald, G; Kelly, C; Coughlan, JJ; Curtin, R; Kerley, R; Moore, D; Loo, B; Waters, M; Mulcahy, D
Abstract : Background: Limited data is available regarding real-world prescribing strategies in patients with an indication for oral anticoagulation (OAT) who undergo percutaneous coronary intervention (PCI). Most current guidelines recommend a period of triple therapy (TOAT) with OAT and dual antiplatelet (DAPT) agents but high quality evidence regarding agent choice and duration is limited and evidence based guidelines sparse. Aim: To analyse the appropriateness of OAT and anti-platelet strategies post PCI in a real-world cohort of patients in two academic teaching hospitals. Methods: 103 patients with an indication for OAT who underwent PCI in two university teaching hospitals were retrospectively analysed. Patients were divided into three cohorts; bleeding risk predominant (HASBLED > CHADSVASC), equipoise risk (CHADSVASC = HASBLED) and ischemic risk predominant (CHADSVASC > HASBLED). Decision making regarding OAT and antiplatelet therapy was divided into three categories: DAPT, dual therapy (OAT with a single antiplatelet agent) and triple therapy (OAT with DAPT). Results: Ninety-seven patients (94.2%) received triple therapy, four received dual therapy (OAC + single antiplatlet) (3.9%) and two received DAPT alone (1.9%) (table 1 ). Patients with predominant bleeding risk were significantly less likely to receive Triple Therapy (75% vs. 95.7% vs. 95.8%, p<0.05). Apixaban was the most common OAT (46 patients) which in the majority of cases was prescribed at a potentially inappropriately reduced dose of 2.5 mg BD (37/46, 80.4%). The MACE, bleeding and all-cause mortality rates did not differ significantly between groups (table 2 ). Duration of therapy for the various groups are outlined in figure 1 . Discussion: Our study demonstrates the widespread use of triple therapy in two Irish academic hospitals. DOACs were prescribed in most cases at reduced doses, currently a strategy with insufficient data to support widespread use. Significant heterogeneity exists regarding treatment strategies for patients undergoing PCI with an indication for OAT. This is likely due to physician experience and risk vs benefit analysis which may not be explicitly incorporated into guidelines. Further study is needed to improve evidence-based management in this area and develop robust guidelines to assist adherence to best practice evidence based treatment.